(untitled) (Concept: The Journal of Contemporary Community Education Practice Theory, 2023)
When discussing the Special Issue on care, I leapt at the chance to include a piece on young carers. Mae Shaw and I arranged interviews with colleagues at Edinburgh Young Carers in order to gain insight into their thoughts about young carers - the tensions and opportunities. Needless to say, what started as a simple exercise involving 3 questions evolved into a far more stimulating experience for us all.